2000
DOI: 10.1091/mbc.11.10.3353
|View full text |Cite
|
Sign up to set email alerts
|

Matricellular Proteins as Modulators of Cell–Matrix Interactions: Adhesive Defect in Thrombospondin 2-null Fibroblasts is a Consequence of Increased Levels of Matrix Metalloproteinase-2

Abstract: Thrombospondin 2 (TSP2)-null mice, generated by disruption of the Thbs2 gene, display a variety of connective tissue abnormalities, including fragile skin and the presence of abnormally large collagen fibrils with irregular contours in skin and tendon. In this study we demonstrate that TSP2-null skin fibroblasts show a defect in attachment to a number of matrix proteins, and a reduction in cell spreading. To investigate the molecular mechanisms responsible for these abnormal cell-matrix interactions, we compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
155
0
3

Year Published

2001
2001
2008
2008

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 175 publications
(168 citation statements)
references
References 43 publications
10
155
0
3
Order By: Relevance
“…Pro-MMP2 by APMA-We recently reported that TSP2-null fibroblasts have a marked adhesive defect when plated on a number of protein substrates, and we showed that this defect resulted from a 2-fold increase in MMP2 protein in the conditioned media of the cells (6). The adhesive defect was corrected by inhibitors of MMP2, by transfection of a full-length TSP2 cDNA gene into the cells, or by long term preincubation with recombinant TSP2 but not by adsorption of TSP2 to tissue culture plastic.…”
Section: Tsp2 Does Not Inhibit Mmp2 Activity or The Activation Ofmentioning
confidence: 85%
See 4 more Smart Citations
“…Pro-MMP2 by APMA-We recently reported that TSP2-null fibroblasts have a marked adhesive defect when plated on a number of protein substrates, and we showed that this defect resulted from a 2-fold increase in MMP2 protein in the conditioned media of the cells (6). The adhesive defect was corrected by inhibitors of MMP2, by transfection of a full-length TSP2 cDNA gene into the cells, or by long term preincubation with recombinant TSP2 but not by adsorption of TSP2 to tissue culture plastic.…”
Section: Tsp2 Does Not Inhibit Mmp2 Activity or The Activation Ofmentioning
confidence: 85%
“…Dermal fibroblasts, isolated from adult animals, also show an adhesive defect in vitro that is most evident when cells are plated on a variety of pure protein substrates in the absence of serum. Adhesion was restored by prolonged (48 h) incubation of TSP2-null cells with recombinant mouse TSP2 or by transfection with a TSP2 cDNA gene (6). The basis for this adhesive defect was recently investigated and was shown by zymography to result from an increase in matrix metalloproteinase 2 (MMP2) levels in both the conditioned media and cell layers of cultured cells (6).…”
mentioning
confidence: 99%
See 3 more Smart Citations